Warum etwas wird: Zur Selbstorganisation rekursiver Erprobungen im Möglichkeitsraum - Grössing, Gerhard (Österreichische Zeitschrift für Geschichtswissenschaften, 2002)
Development and dissolution are basic characteristics of a wide variety of systems. The latter include biological ones, but also non-living systems as, for example, geological onesand, of course, also social systems. As we have known for a long time, processes of decay in the physical and biological domains are governed by the law of entropy. However, processes related to the emergence of new structures, or of organizational forms, have become an issue of broad scientific investigation only during the last third of the twentieth century. Based on the studies of the phenomenon of self-organization (or emergence), new approaches to understanding the abstract machines behind structure generating and structure changing processes have emerged in recent years. This has led to the design of nonlinear models for general systems, which, among others, are also applicable to historical processes. (See, for example, M. de Landa, »A Thousand Years of Nonlinear History «. ) Some of the contemporary instruments used to simulate correspondingly complex systems on the computer are briefly reviewed, e. g., genetic algorithms and cellular automata. lt is shown that there is a solid foundation for explaining the emergence of an »arrow of time« in biological, and even in social systems. Here, decisive roles are attributed to a) the presence of recursive processes (replications, for example) and b) significant fluctuations around mean values. Such systems can often be characterized by the self-organization of recursive »probes« in the space of poten-tial forms of their organization. In sufficiently complex systems, the latter may emerge by means of their intrinsic dynamics, i. e., independent of any external control mechanisms.